Analise comparativa da vazão do rio Madeira antes e depois da operação da UHE Santo Antônio - SILVA, Adriane Franco da (2021)
Based on the debate on the influence of flow regularization from the installation of Hydroelectric Plants in rivers, this article aims to analyze the behavior of the flow downstream of the Santo Antônio Hydroelectric Plant, located in the Amazon, and to identify possible changes in the hydrological regime, comparing the scenarios after the plant's operation (post-operation period) and the natural regime (pre-operation period). For this purpose, fluviometric data from the National Water Agency (ANA) were used, and as changes analyzed based on the reference flows Q7,10, Q50, Q90 and Q95, in addition to maximum and averages calculated with the help of the SisCAH 1.0 software. Possibly, because it was projected at run-of-river, the results showed small changes in the fluviometric regime after the operationalization of the HPP, when compared to the behavior in plants with large reservoirs. Among the main changes found, we can highlight the increase in average flows, caused by atypical flows in the period, as occurred in 2014, in addition to the reduction in Q95 (± 4.8%) and the increase in Q50 (± 13%), which may be related to the low capacity of regularization of the HPP, combined with the highly seasonal behavior of the combination in the basin. In this sense, it is recommended that future work be carried out, analyze what are the possible impacts of these changes, both from a socio-environmental point of view, as well as an economic one for the region.